GAME-BASED READING INSTRUCTION IN EARLY GRADES - Tashmatova Mahira Takhirovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Game-based reading instruction has become one of the most effective approaches in modern primary education. Early grade learners require engaging and interactive methods that support literacy development while maintaining motivation and emotional involvement. Traditional reading instruction often depends on memorization and repetitive exercises, whereas game-based learning combines educational goals with enjoyable activities. This article discusses the importance of game-based reading instruction in early grades, theoretical foundations of play-based learning, types of educational games used in literacy classrooms, benefits of game- based methods, the role of teachers and parents, digital learning opportunities, and challenges related to implementation. The article also presents practical recommendations for improving literacy instruction through games and interactive learning strategies.